E-learning networked environments and architectures : a knowledge processing perspective - Pierre, Samuel. (Advanced information and knowledge processing., 2007)
Over the last decade researchers and practitioners have developed a wide range of knowledge related to e-learning. This book provides state-of-the-art e-learning networked environments and architectures carried out over the last few years from a knowledge management perspective. The book is organized into four parts: After an introductory chapter which attempts to characterize the e-learning environments, Part I exposes the problems of building knowledge scenarios followed by Part II which analyzes the process of building knowledge environments. Part III summarizes the principles, methods and issues related to the design of knowledge networks and finally Part IV addresses the problem of retrieving resources and knowledge from networked environments. Presenting a wide-ranging survey of methods and applications from contributors from around the world, this book will be a valuable resource for researchers, practitioners and graduates.